2013
DOI: 10.1007/s00253-013-4813-1
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization, virulence, and immunogenicity of Edwardsiella tarda LSE40 aroA mutant

Abstract: Bacterial aro mutants are frequently used as live attenuated vaccines for domestic animals. In this study, we characterized Edwardsiella tarda strain LSE40 with a deletion in the aroA gene. In addition to autotrophy, the aroA mutant appeared to have delayed cell division and reductions in its swarming motility, biofilm formation, and production of translocator proteins in the type III secretory system. The mutant exhibited high virulence attenuation in turbot fish, Scophthalmus maximus (L.), where the 50 % let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…We speculate that the low immunization dose might have been responsible for the limited protection observed. However, other studies have also shown that fully attenuated bacterial strains such as the Edwardsiella tarda aroA mutant fail to provide effective protection against virulent challenge even at a high dose of immunization, probably because of reduced immunogenicity or loss of protective antigens [ 59 61 ]. Therefore, it is vital to retain or improve bacterial immunogenicity while achieving attenuation through the deletion of virulence regulators.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the low immunization dose might have been responsible for the limited protection observed. However, other studies have also shown that fully attenuated bacterial strains such as the Edwardsiella tarda aroA mutant fail to provide effective protection against virulent challenge even at a high dose of immunization, probably because of reduced immunogenicity or loss of protective antigens [ 59 61 ]. Therefore, it is vital to retain or improve bacterial immunogenicity while achieving attenuation through the deletion of virulence regulators.…”
Section: Discussionmentioning
confidence: 99%
“…A non‐polar deletion of the asd g ene strain was generated in E . piscicida LSE40 using a published method (Mo et al., 2013). The primers used for mutant construction are listed in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, biofilm-related genes have dual functions: normal cellular and biofilm formation functions. The first group of genes shown to interfere with biofilm formation involve biosynthetic genes, such as those involved in the biosynthesis of the LPS ( wibT, gne , and ugd ) [ 48 ] and aromatic amino acids ( aroA ) [ 49 ]. Other biosynthetic genes may directly interfere with the synthesis of extracellular components needed for biofilm formation.…”
Section: Edwardsiella As a Free-living Aquatic Bacteriummentioning
confidence: 99%